Perbandingan produksi dan kualitas susu kambing Peranakan Ettawa pada dua peternakan yang berbeda di Kota Batu berdasarkan komposisi pakan - Rahmi, Chintyadhevi Aulia; Harijani, Nenny; Suwarno, Suwarno; Budiarto, Budiarto; Anam Al Arif, Mohammad; Warsito, Sunaryo Hadi (Ovozoa: Journal of Animal Reproduction, 2021)
This research aims to compare the production and quality of Ettawa crossbreed goat milk  from two different husbandries in Batu based on the composition of the feed. This research used Ettawa crossbreed goat milk samples from the 3rd week period of the second lactation at Madukara and Green farms with three replicates collected within 3 days in a row. Proximate analysis showed that feed P1 composed of 51.53% dry matter; 2.74% ash; 10.94% crude protein; 4.93% crude fat; 16.34% crude fiber; 16.58% nitrogen-free extract (NFE) and 41.85% total digestible nutrients (TDN) with a total weight of feed consumed 5.1 kg/day per lactating doe; whereas P2 feed composed of 63.94% dry matter; 6.32% ash; 11.38% crude protein; 4.62 % crude fat; 16.31% crude fiber; 25.31%  NFE and  49.23% TDN with a total weight of feed consumed 5.46 kg/day per lactating doe. The data obtained are  presented descriptively in tables. The results of this research  showed that the total consumption of P1 ration resulted in a higher milk production ((892.22±99.92 vs 661.11±19.39)  mL/day per doe). In addition, in does fed P1 ration, milk fat content was higher ((5.68±0.21 vs 3.42±0.24)%) and dry matter was also higher ((14.4±0.36 vs 12.14±0.25)%).